4th National Congress of the Bulgarian Society for Dermatologic Surgery, Sofia, 12th March 2022 with main topics: one step melanoma surgery and drug induced melanoma - Tchernev, Georgi; Oliveira, Nikhil; Kandathil, Lorraine Joseph; Patterson, James W.; Cardoso, Jose Carlos; Kordeva, Simona; Pidakev, Ivan; Stavrov, Konstantin (Dermatology Reports, 2022)
Not available